ULAMA-ULAMA TERKEMUKA DI TAPANULI SELATAN DAN UPAYA KADERISASI (Jurnal AL-MAQASID: Jurnal Ilmu Kesyariahan dan Keperdataan, 2016)
This study describes 3 types of Islamic religious leader. The first is a aperson who knows  Allah with all His orders. The second is a person who knows Allah but do not know His orders. And the third is a person who knows Allah but do not know Allah at all. A person who is really afraid of Allah is ones who knows Allah with all His orders and prohibitions. In line with famous Islamic religious leaders in South Tapanuli, the writer only describes two well-known people namely Syekh Ali Hasan Ahmad and SyekhMusatafaHusein who built MustafawiyahPurbaBaru Islamic Centre School.